Feijão-Caupi na região imediata de Bragança, Pará: uma proposta de produção sustentável - ANGELO, Kelly Borges (2020)
The production of cowpea (Vigna unguiculata (L.) Walp) in the Immediate Region of Bragança in northeastern Pará, composed of the municipalities Bragança, Viseu, Santa Luzia do Pará, Tracuateua, Augusto Corrêa and Cachoeira do Piriá, have been facing difficulties due to several factors, and among them stand out, the environmental with the degradation of the cultivation areas and the absence of public policies that act in the implementation of new biotechnologies that with their viability , may improve productivity. Taking into account these local problems, this study was implemented with the aim of raising information together with family farmers about the productive problems of local cowpea, and the proposition of sustainable alternative practices to improve their productivity in the region. The first chapter deals with a bibliographic survey on the general aspects of cowpea, its interactions with arbuscular mycorrhizal fungi (AMF) and with conservation systems that benefit these soil microorganisms, with organic fertilization and inoculation processes with native mycorrhizal fungi. On the other hand, the second chapter deals with the current conjuncture of cowpea production obtained by family farmers in the Immediate Region of Bragança in the State of Pará, focusing on socioeconomic aspects, seeking to understand their difficulties in obtaining the improvement of quality of life in the field. The third chapter, in turn, brings an analysis of cowpea performance under interaction of organic fertilization and mycorrhizal inoculation with native fungus, from the inoculum soil of the brachiaria trap plant, as a proposal of sustainable alternative practice for optimizing the productivity of the caupi bean in the region. The use of inoculants based on beneficial microorganisms such as native AMF, can contribute to the construction of sustainable agriculture by family farmers subsidizing the socio-economy of the region, such as the induction of employment and income for these families of farmers, capable of influencing the resumption of the production of cowpea which is a culture of great economic and cultural value , reacquiring its local cultural identity.